The development of the Chinese legal profession since 1978 - Hu, Juan (1998)
This thesis focuses on introducing the development of, and changes in, the Chinese legal profession over this past twenty years, analysing the reasons that led to these changes, and considering both theoretical and practical problems. The Chinese legal profession has developed considerably since 1978 when the reform and opening up movement was begun. Major changes have taken place in the lawyer’s social status, business, work institutions and in the supervision system. Compared with the end of the 1970s, the legal profession nowadays is much more commercialised and professional. The changes have a symbiotic relationship with the changes in Chinese society: economic and ideological changes have transformed the role of lawyers and the law, which have in turn led to changes in society. The transformation of the Chinese society is still going on, and corresponding future changes are expected in the legal profession